2022
DOI: 10.55519/jamc-02-9491
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Adiponectin Levels With Glycaemic Status in Pregnant Women

Abstract: Background: Adiponectin plays an important role in glucose metabolism and released in response to insulin. It helps to decrease glucose levels and insulin resistance; however, this relation is not been studied in pregnant ladies. Objective was to determine serum adiponectin level and glycaemic status in pregnant women belonging to Peshawar, Khyber Pakhtunkhwa (KPK) and to find any possible relationship between them. Methods: Hundred pregnant women with gestational diabetes mellitus (GDM) and 100 healthy pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 0 publications
1
15
0
5
Order By: Relevance
“…Feeding rats with the standard stuff made of Pyracantha fruit dry powder can significantly reduce the contents of blood lipids in the body and improve blood rheology, avoid blood lipid deposition and thrombosis, and protect the myocardium, which is beneficial to the cardiovascular system-certain protective effect. Dahri et al (2005) found that Pyracantha can significantly increase the blood HDL-C level in normal rats, and it can also reduce TC to a certain extent and has the effect of improving academic year.…”
Section: Hypolipidemic Effectmentioning
confidence: 95%
See 1 more Smart Citation
“…Feeding rats with the standard stuff made of Pyracantha fruit dry powder can significantly reduce the contents of blood lipids in the body and improve blood rheology, avoid blood lipid deposition and thrombosis, and protect the myocardium, which is beneficial to the cardiovascular system-certain protective effect. Dahri et al (2005) found that Pyracantha can significantly increase the blood HDL-C level in normal rats, and it can also reduce TC to a certain extent and has the effect of improving academic year.…”
Section: Hypolipidemic Effectmentioning
confidence: 95%
“…Dahri et al. (2005) found that Pyracantha can significantly increase the blood HDL‐C level in normal rats, and it can also reduce TC to a certain extent and has the effect of improving academic year.…”
Section: Biological and Medicinal Propertiesmentioning
confidence: 99%
“…In der Literatur finden sich übersichtliche Anzahlen von sogenannten Shuntnephritiden, wenngleich die Inzidenz mit bis zu 4,7 % der implantierten VA-Shunts häufig ist [1]. Endokarditiden können begleitend auftreten [2].…”
Section: Hintergrundunclassified
“…Als Erreger finden sich häufig Staphylokokken 2 , 3 , seltener Corynebakterien 4 . Pathophysiologisch handelt es sich zumeist um mesangiokapillär-proliferative Glomerulonephritiden 14 , welche durch zirkulierende Immunkomplexe und Plasmaproteine des Komplementsystems verursacht werden 4 . Die Therapie besteht zumeist in einer Explantation des infizierten Shunts und einer Shuntneuanlage, wenn möglich als VP-Shunt, mit flankierender Antibiose.…”
Section: Hintergrundunclassified
See 1 more Smart Citation